(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
Female birds whose bodies contain environmental contaminants produce eggs with shells that are likewise contaminated, making bird eggshells appropriate indicators for monitoring environmental toxins. Common contaminants include organic mercury compounds, especially methylmercury, which are known to bioaccumulate and biomagnify in the food chain. Black storks (Ciconia nigra) predominantly consume fish and are thus at risk for high mercury intake. In this study, we used eggshells of black storks as a proxy to reconstruct the concentration levels and distribution of mercury, a well-known toxic element, in various parts of Latvia. Preliminary analyses have shown that deposition levels of mercury vary in different parts of the eggshell. Specifically, the shell and shell membrane differ in their level of mercury contamination by an average factor of nine; therefore, we measured the mercury content in these components separately whenever possible. We analysed 34 eggshell samples from nesting sites in Latvia using an atomic absorption spectrometer with Zeeman correction Lumex RA-915M and its attachment for pyrolytic combustion. We found that mercury concentrations varied from 5 to 22 ng/g in eggshells and from 42 to 293 ng/g in shell membranes. We discuss possible contamination sources and reasons behind this disparity.